Intrastrand triplex DNA repeats in bacteria: a source of genomic instability - Holder, Isabelle T. (Nucleic Acids Res, 2015)
Repetitive nucleic acid sequences are often prone to form secondary structures distinct from B-DNA. Prominent examples of such structures are DNA triplexes. We observed that certain intrastrand triplex motifs are highly conserved and abundant in prokaryotic genomes. A systematic search of 5246 different prokaryotic plasmids and genomes for intrastrand triplex motifs was conducted and the results summarized in the ITxF database available online at http://bioinformatics.uni-konstanz.de/utils/ITxF/. Next we investigated biophysical and biochemical properties of a particular G/C-rich triplex motif (TM) that occurs in many copies in more than 260 bacterial genomes by CD and nuclear magnetic resonance spectroscopy as well as in vivo footprinting techniques. A characterization of putative properties and functions of these unusually frequent nucleic acid motifs demonstrated that the occurrence of the TM is associated with a high degree of genomic instability. TM-containing genomic loci are significantly more rearranged among closely related Escherichia coli strains compared to control sites. In addition, we found very high frequencies of TM motifs in certain Enterobacteria and Cyanobacteria that were previously described as genetically highly diverse. In conclusion we link intrastrand triplex motifs with the induction of genomic instability. We speculate that the observed instability might be an adaptive feature of these genomes that creates variation for natural selection to act upon.